Adsorption kinetics and modeling of H2S by treated waste oil fly ash. (1st February 2019) - Aslam, Zaheer; Hussein, Ibnelwaleed A.; Shawabkeh, Reyad A.; Parvez, Mohammad Anwar; Ahmad, Waqar; Ihsanullah,
ABSTRACT: Waste oil fly ash (OFA) collected from disposal of power generation plants was treated by physicochemical activation technique to improve the surface properties of OFA. This synthesized material was further used for potential hydrogen sulfide (H2 S) adsorption from synthetic natural gas. The raw OFA was basically modified with a mixture of acids (20% nitric acid [HNO3 ] and 80% phosphoric acid [H3 PO4 ]), and it was further treated with 2 M potassium hydroxide (KOH) to enhance the surface affinity as well as surface area of synthesized activated carbon. Correspondingly, it enhanced the adsorption of H2 S. Crystallinity, surface morphology, and pore volume distribution of prepared activated carbon were investigated using X-ray diffraction (XRD), scanning electron microscopy (SEM), and Brunauer-Emmett-Teller (BET) analyses. Fourier transform infrared (FTIR) study was also performed to identify the functional groups during different synthesis stages of modified activated carbon. The Langmuir, Freundlich, Sips, and dual-site Langmuir (DSL) models were used to study the kinetic and breakthrough behavior of H2 S adsorption over alkali-modified activated carbon. Modeling results of isotherms indicated that OFA has dual sites with high and low affinity for H2 S adsorption. The Clark model, Thomas model, and Yoon-Nelson model were used to examine the effects of flow rate and inlet concentration on the adsorption of H2 S. Maximum uptake capacity of 8.5 mg/g was achieved at 100 ppm inlet concentration and flow rate of 0.2 L/min. Implications : Utilization of worthless oil fly ash from power plant is important not only for cleaning the environment but also for solid waste minimization. This research scope is to eradicate one pollutant by using another pollutant (waste ash) as a raw material. Chemical functionalization of synthesized activated carbon from oil fly ash would lead to attachment of functional groups of basic nature to attract the acidic H2 S. Such type of treatment can enhance the uptake capacity of sorbent several times.